Are there industrial and agricultural convergence clubs in China? - Jenni Pääkkönen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper discusses growth differentials of Chinese provinces geared to agricultural activities and those focusing on industrial production over three decades of economic reform. Following trade theory and endogenous growth theory, we suggest that the fundamental differences between regions arise from their resource allocations at the start of reforms. Thus, capital-abundant regions have tended to specialize in industrial production, while the labor-abundant regions have concentrated on labor-intensive pro- duction (agriculture). Many of China.s agricultural provinces suffer from oversupplies of labor, which has led large numbers of people to migrate within the country to work in non-farming sectors of economy. We show that provinces with high shares of industrial production (the industrial club) have converged, and that agricultural provinces shifting to industrial production have been catching up to initially industrialized provinces. Provinces that have stayed with an agricultural strategy (the agricultural club) show no evidence of convergence and appear to have been left behind in terms of economic development.
URN:NBN:fi:bof-201408071899
Keywords: O17; O40; O57; 330; Growth; Agriculture; Convergence